Pospublicidad: la era de la comunicación global - Costa Solà–segalés, Joan (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
Postmodernism, posthistory, postindustrialism are expressions that define our time concerning concepts and methods that have already been overcome. The «post-age» concept is not enough to define our new reality due to the fact of multiple causes. There have been deep changes in the area of bussines and management. All responsibilities now point the enterprise; not the product, nor the brand. The enterprises are conceived as a whole. Deontological codes, reputation, ethics and social accountability have more and more importance, whereas advetising effectivity decreases because of the increasing ad saturation and the difficulties of measuring rentability.